If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 7b = 35 Solving 7 + 7b = 35 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 7b = 35 + -7 Combine like terms: 7 + -7 = 0 0 + 7b = 35 + -7 7b = 35 + -7 Combine like terms: 35 + -7 = 28 7b = 28 Divide each side by '7'. b = 4 Simplifying b = 4
| -45=7-2p | | 19=23-4b | | Log(x+14)-log(x+6)=logx | | t-3=13 | | 13+7v=97 | | 3(x-7)=x-6 | | 105-3h=69 | | 6x+16=5x+9 | | 1.5(x-24)=13 | | f(-3)=6x^2-12 | | 4(3z-5)+9(5z+4)= | | 16=3d+1 | | 5-25x=105 | | 99=7j+1 | | x^2-5y^2=3 | | 2=3y-18-5x | | x^2-9+2xy+y+5=10 | | 67=25+6s | | -13+a=-6 | | 15-2x-7=14 | | 2-2m=8 | | 67=256s | | -x(x^2+4)= | | 7s-10=46 | | 26=3u-64 | | E^3-2x=10 | | 2y+4=4y-6 | | 38k=2204 | | 60x-40=50x | | 6x-1+8x=3x+3-5x | | 19y=95 | | g+11=-3 |